Mannose-binding lectin does not act as an acute-phase reactant in adults with community-acquired pneumococcal pneumonia - Perez-Castellano, M (Blackwell Science Inc, 2006)
The objective of this work was to study the role of mannose-binding lectin (MBL) and C-reactive protein (CRP) in pneumococcal pneumonia, to determine whether MBL acts as an acute-phase reactant and whether the severity of the disease correlates with MBL levels. The study comprised 100 patients with pneumococcal pneumonia. The pneumonia severity score was calculated and graded into a risk class of mortality (Fine scale). The MBL genotypes and the levels of MBL and CRP at the acute and recovery phases were determined. Fifty patients with the wild-type MBL genotype showed higher MBL levels in each phase (P < 0·001) and an increased risk to developing bacteraemia, odds ratio (OR) 2·74, 95% confidence interval (CI) 1·01–7·52) (P = 0·02), but this did not correlate with the pneumonia severity class. CRP levels in the acute phase, 79·53 mg/l [standard deviation (s.d.) 106·93], were higher in the subjects with positive blood cultures (P = 0·003), and remained higher [20·12 mg/l (s.d. 31·90)] in the group of patients with an underlying disease (P = 0·01). No correlation was observed between the levels of MBL and CRP in each phase, or with the pneumonia severity score. We cannot conclude that MBL acts uniformly as an acute-phase reactant in pneumococcal pneumonia. MBL levels do not correlate well with the severity of the pneumonia. The risk of developing bacteraemia could be enhanced in individuals with the wild-type MBL genotype.